غیر مسلموں سے تعاون واستفادہ کے ایجابی وسلبی پہلو - Mahmood, Muddassrah; Shabbir, Dr. Asia (Al-Irfan, 2022)
Today existential questions of Muslims in current situation is to interpret the Islamic laws in order to help Muslim congregations save face and faith . Since the era of globalization, it is an opportunity for global Islamic resurgence as Muslims cannot avoid Non-Muslim society of the world. To find the solution to current situation lies in the light of Seerah of Holy Prophet (S.A.W) as he preached tolerance for all religions of the world. So he managed some contracts with Jews of Madina very wisely and drew benefits from the Non-Muslims within the scope of Islamic teaching. Thus in this current situation Quran and Sunnah of Prophet Muhammad (S.A.W ) act as a mental bulwark against various element that would damage Muslim community from within or produce chaos and oblivion as end goals. The methodology of my research is analytical and deductive. I will highlight that there is complete liberty in seeking benefits from Non-Muslims by maintaining admissible and inadmissible aspects in Islam. Keywords: Mulims, Non-Muslims, Seerah, globalization, benefits.